2021
DOI: 10.3390/metabo11090632
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Dietary Intervention Improved the Serum Lipid Signature towards a Less Atherogenic Profile in Patients with Rheumatoid Arthritis

Abstract: Diet is a major modifiable risk factor for cardiovascular disease (CVD). One explanation for this is its effect on specific lipids. However, knowledge on how the lipidome is affected is limited. We aimed to investigate if diet can change the new ceramide- and phospholipid-based CVD risk score CERT2 and the serum lipidome towards a more favorable CVD signature. In a crossover trial (ADIRA), 50 patients with rheumatoid arthritis (RA) had 10 weeks of a Mediterranean-style diet intervention or a Western-style cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…CVD is the leading cause of death in patients with RA and occurs more often in this patient group than in the general population ( 36 ). We recently demonstrated that a Mediterranean-like diet rich in unsaturated fatty acids as well as fiber improved blood lipid profiles in patients participating in the ADIRA trial, possibly lowering the risk for atherogenesis ( 37 , 38 ). Furthermore, calcium and vitamin D play an important role in bone health.…”
Section: Discussionmentioning
confidence: 99%
“…CVD is the leading cause of death in patients with RA and occurs more often in this patient group than in the general population ( 36 ). We recently demonstrated that a Mediterranean-like diet rich in unsaturated fatty acids as well as fiber improved blood lipid profiles in patients participating in the ADIRA trial, possibly lowering the risk for atherogenesis ( 37 , 38 ). Furthermore, calcium and vitamin D play an important role in bone health.…”
Section: Discussionmentioning
confidence: 99%
“…Our lipidomic results indicate that hepatic CE decreases, while the bile acids and steroid hormones increase (mimicking CD-fed mice), while adipocytes from visceral and subcutaneous depots increased PUFA-containing DG, TG, and LPC; i.e., the effects of dietary intervention in the liver are quantitative, but more qualitative in adipocytes. Caloric restriction per se does not modify the lipid composition, but the type of diet may determine the qualitative lipid aspects such that dietary sources enriched with PUFA modify the phospholipid plasma membrane composition, promoting better metabolic outcomes, than SFA-enriched diets [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several intervention trials have studied the effect of diet on ceramides and in relation to difference health outcomes. Since only one study was performed in patients with AIRDs [ 178 ], we discuss here the effect of diet in healthy, overweight and individuals with increased CVD risk.…”
Section: Dietary Interventions As Anti-ceramide Treatmentsmentioning
confidence: 99%
“…In the only RCT using participants with an AIRD diagnosis, Lindqvist and associates [ 178 ] applied a dietary cross-over intervention to improve the serum lipid profile of patients with RA, towards a less atherogenic one. The Anti-Inflammatory Diet In Rheumatoid Arthritis (ADIRA) trial showed that, although several components of the ceramide-and phospholipid-based CVD risk score (CERT2) were improved post-intervention, no significant difference was observed in the CERT2 of the intervention-receiving arm, compared to the control diet [ 178 ]. Furthermore, the trial revealed that a “healthier” composition of cholesteryl esters, phosphatidylcholines, alkenylphosphatidylcholines, TG and alkylphosphatidylcholines was apparent after the MD intervention was conducted [ 178 ].…”
Section: Dietary Interventions As Anti-ceramide Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation